METODE DRILL KAANGGEN NINCAPANG KAWAGEDAN NEMBANGANG PUPUH SEMARANDANA SISIA KELAS XI ILMU BAHASA DAN BUDAYA SMA NEGERI 1 KUBUTAMBAHAN - Angga Kukuh,I Kd; Ida Ayu Putu Purnami; I.B.Putra Manik Aryana (Universitas Pendidikan Ganesha, 2019)
This research has purpose to explain (1) how to implement the steps in using the drilling method to improve ablelity to sing pupuh semarandana for grade 11 th of SMA Negeri 1 Kubutambahan in major art and culture, (3) to know the students’ opinion about using the drilling method which using to improve ablelity to sing pupuh semarandana for the students grade 11 th of SMA Negeri 1 Kubutambahan in major art and culture the research used class lmplementation research. The subject of the research were the students grade 11 th.. while the object of the resarsch was drilling method. The Collecting data used observation method ,test method, questionnaire, the data analysis used descriptive and qualitative data analysis technique And descriptive quantitative data analysis technique. The result of the research showed that (1) the step of learning used drilling method which used to develop ablelity to sing pupuh semarandana for the students grade 11 th of SMA Negeri 1 kubutambahan in major art and culture which based on the lesson plan was made by the teacher.(2) the drilling method could improve the students’ ablelityty sing pupuh semarandana., there were improvements the result of the students’ test after the first section done., the students’ score approximately reached 73,23. While the second section reached 86, 64. (3) the students’ opinion about the drilling method were very agree in first section, 10 students (29,41%) gave their opinion very agree, 23 students (67,64%) were agree and 1 student (2,94%) less agree. The other hand the second section showed that 26 students (76,47%) were very agree, and 8 students (23,52%) were agree.Key words: drilling method, singing, pupuh semarandana.